In silico modeling for quick prediction of inhibitory activity against 3CLpro enzyme in SARS CoV diseases. Issue 3 (2nd February 2022) - De, Priyanka; Bhayye, Sagar; Kumar, Vinay; Roy, Kunal
Abstract: As of 2 September 2020, the 2019 novel coronavirus or SARS CoV-2 has been responsible for more than 2, 56, 02, 665 infections and 8, 52, 768 deaths worldwide. There has been an urgent need of newer drug discovery to tackle the situation. Severe acute respiratory syndrome-associated coronavirus 3C-like protease (or 3CL pro ) is a potential target as anti-SARS agents as it plays a vital role in the viral life cycle. This study aims at developing a quantitative structure–activity relationship (QSAR) model against a group of 3CL pro inhibitors to study their structural requirements for their inhibitory activity. Further, molecular docking studies were carried out which helped in the justification of the QSAR findings. Moreover, molecular dynamics simulation study was performed for selected compounds to check the stability of interactions as suggested by the docking analysis. The current QSAR model was further used in the prediction and screening of large databases within a short time. Communicated by Ramaswamy H. Sarma